Participation in sports practice and motor competence in preschoolers - Daniel da Rocha Queiroz; Alessandro Hervaldo Nicolai Ré; Rafael dos Santos Henrique; Mariana de Sousa Moura; Maria Teresa Cattuzzo (Universidade Estadual Paulista (UNESP), 2014)
Recent theoretical model suggests that motor competence during early childhood is related to one's current and future health status and that practicing sports seems to be playing a special role in creating such competence. This study aimed to compare performance in gross motor skills among preschoolers participating in regular sports practice (SP) and those not participating (NSP), including comparisons by gender. The study uses secondary data from a population-based study of performance regarding the locomotor and object control skills of preschoolers (3 to 5 years old). Preschoolers were assigned to groups SP or NSP, paired by age and sex according to skills: locomotor (n = 54; 30 boys) or object control (n = 37; 17 boys). Analysis of variance showed that the SP group outperformed the NSP one, and there were gender differences only within SP group. Starting to practice sports during early childhood helps to build motor competence and benefits both genders.